2007
DOI: 10.17221/2275-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Poultry meat production as a functional food with a voluntary n-6 and n-3 polyunsaturated fatty acids ratio

Abstract: From the aspect of human health, the fatty acid (FA) composition of meat products is an important parameter of meat quality. With the recognition that the groups of polyunsaturated fatty acids (PUFA) each play their own metabolic roles in health promotion, the role of the polyunsaturated/saturated FA ratio has decreased while the importance of the total n-6/n-3 ratio or even only linoleic acid/α-linolenic acid ratio has increased (Bruckner, ex Dublecz et al., 2004).In human diets, there is a considerable lack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
2
5
0
4
Order By: Relevance
“…Both n‐3 and n‐6 levels were affected by flaxseed oil consumption, but total n‐3 content of thigh increased with a higher rate that resulted in a decreased n‐6:n‐3 ratio from 4.50 to 1.95 after 42 days of feeding diet contained flaxseed oil. Similar results were reported previously .…”
Section: Resultssupporting
confidence: 93%
“…Both n‐3 and n‐6 levels were affected by flaxseed oil consumption, but total n‐3 content of thigh increased with a higher rate that resulted in a decreased n‐6:n‐3 ratio from 4.50 to 1.95 after 42 days of feeding diet contained flaxseed oil. Similar results were reported previously .…”
Section: Resultssupporting
confidence: 93%
“…Ceylan et al [89] evaluated the effect of dietary supplementation on two levels (15 g/kg and30 g/kg diet) of SO, rapeseed oil, and LO for 12 weeks in laying hens. They concluded that egg production, egg weight, feed intake, FCR, and live weight were not significantly affected by the treatments.…”
Section: Improving Egg Quality and Nutritional Value Of Eggsmentioning
confidence: 99%
“…In recent years the awareness of the importance of a diet in human health has increased. In the Czech Republic, the problem of the better fatty acid profile in meat is often studied in poultry (Schneiderová et al, 2007;Skřivan et al, 2008;Zelenka et al, 2008) and beef cattle (Bureš et al, 2006;Bartoň et al, 2007) but less frequently in pigs. There are important species differences in fatty acid composition.…”
mentioning
confidence: 99%